Perpetual Dispossession: An Exploration of Ownership without Possession - Hall,Matthew; Zhao,Xin (Advances in Consumer Research, 2016)
We examine disruptions in the consumption cycle as possessions are divested of meanings, but never disposed. This perpetual process of dispossession results in legal ownership of objects, without explicit incorporation into the self. Through an ethnographic approach, we examine factors contributing perpetual dispossession and discuss implications for the extended self
Keywords: Marketing